Ventriculo‐arterial coupling detects occult RV dysfunction in chronic thromboembolic pulmonary vascular disease. Issue 7 (3rd April 2017) - Axell, Richard G.; Messer, Simon J.; White, Paul A.; McCabe, Colm; Priest, Andrew; Statopoulou, Thaleia; Drozdzynska, Maja; Viscasillas, Jamie; Hinchy, Elizabeth C.; Hampton‐Till, James; Alibhai, Hatim I.; Morrell, Nicholas; et al.
Abstract: Chronic thromboembolic disease (CTED) is suboptimally defined by a mean pulmonary artery pressure (mPAP) <25 mmHg at rest in patients that remain symptomatic from chronic pulmonary artery thrombi. To improve identification of right ventricular (RV) pathology in patients with thromboembolic obstruction, we hypothesized that the RV ventriculo‐arterial (Ees/Ea) coupling ratio at maximal stroke work (Ees/Eamax sw ) derived from an animal model of pulmonary obstruction may be used to identify occult RV dysfunction (low Ees/Ea) or residual RV energetic reserve (high Ees/Ea). Eighteen open chested pigs had conductance catheter RV pressure‐volume (PV)‐loops recorded during PA snare to determine Ees/Eamax sw . This was then applied to 10 patients with chronic thromboembolic pulmonary hypertension (CTEPH) and ten patients with CTED, also assessed by RV conductance catheter and cardiopulmonary exercise testing. All patients were then restratified by Ees/Ea. The animal model determined an Ees/Eamax sw  = 0.68 ± 0.23 threshold, either side of which cardiac output and RV stroke work fell. Two patients with CTED were identified with an Ees/Ea well below 0.68 suggesting occult RV dysfunction whilst three patients with CTEPH demonstrated Ees/Ea ≥ 0.68 suggesting residual RV energetic reserve. Ees/Ea > 0.68 and Ees/Ea < 0.68 subgroups demonstrated constant RV stroke work but lower stroke volume (87.7 ± 22.1 vs. 60.1 ± 16.3 mL respectively, P  = 0.006) and higher end‐systolic pressure (36.7 ± 11.6 vs. 68.1 ± 16.7 mmHg respectively, P  < 0.001). Lower Ees/Ea in CTED also correlated with reduced exercise ventilatory efficiency. Low Ees/Ea aligns with features of RV maladaptation in CTED both at rest and on exercise. Characterization of Ees/Ea in CTED may allow for better identification of occult RV dysfunction. Abstract : We have used PV‐loop analysis in a porcine model of pulmonary hypertension to define the optimal Ees/Ea coupling ratio for RV maximal efficiency. We have applied this cut‐off to patients with chronic thromboembolic pulmonary disease and detected occult RV dysfunction.